18F-FDG PET/CT and 99mTc-HMPAO-WBC SPECT/CT effectively contribute to early diagnosis of infection of arteriovenous graft for hemodialysis - Medricka, Monika; Janeckova, Jana; Koranda, Pavel; Buriankova, Eva; Bachleda, Petr (Biomedical papers, 2019)
Objective: An arteriovenous graft (AVG) is indicated in hemodialysis patients with failed arteriovenous access. Early treatment of AVG infection is important because an advanced prosthetic infection leads to the removal of the prosthesis. The aim of this study was to evaluate the benefits of 18F-FDG PET/CT and 99mTc-HMPAO-WBC SPECT/CT in early detection of AVG infections. Subjects and Methods: Fifty-one AVGs were evaluated. 18F-FDG PET/CT and 99mTc-HMPAO-WBC SPECT/CT studies were performed at intervals of 10, 20-30, and 40-50 weeks after AVG insertion. Agreement between the imaging methods and reference parameters (i.e. clinical presentation, C-reactive protein and microbiological findings on the hemodialysis cannula extracted after hemodialysis from AVG) was evaluated. Results: The study results showed that focal accumulation of the radiopharmaceuticals can be considered a sign of AVG infection. At 10 weeks after AVG implantation, the focal 18F-FDG findings showed the best agreement with the reference parameters (agreement coefficients AC1 - clinical status: 0.693, CRP: 0.605, cannula microbiology: 0.518, respectively). At 20 to 30 weeks after AVG implantation, the diagnostic value of focal 99mTc-HMPAO-WBC accumulation increased (AC1 coefficients: 0.658, 0.658, 0.408) and was similar to that of focal 18F-FDG uptake (AC1s: 0.656, 0.570, 0.409). Between 40 and 50 weeks since AVG implantation, the diagnostic significance of focal 99mTc-HMPAO-WBC accumulation (AC1 coefficients: 0.771, 0.811, 0.611) slightly exceeded the diagnostic value of focal 18F-FDG accumulation (AC1 coefficients: 0.524, 0.456, 0.569). Conclusion: 18F-FDG PET/CT and 99mTc-HMPAO-WBC SPECT/CT can both serve as important tools contributing to early diagnosis of AVG infection.
Keywords: 18F-FDG PET/CT; 99mTc-HMPAO-WBC SPECT/CT; infection; arteriovenous graft; hemodialysis